Unravelling Conceptions of Learning - Xiantong Zhao (International Journal of Asian Education, 2022)
The aim of this article is to provide a systhesised review of the literature on conceptions of learning in both the western and Asian contexts. It follows Cooper’s (1988) steps for synthesising the literature. The review begins by examining definitions of conceptions of learning, a process that enables analysis of the quantitative and qualitative dichotomy. It then moves to the potential interrelationship between various conceptions, more specifically, the hierarchical structure proposed by researchers. In the following section, it explores the significance of conceptions of learning by examining the close relationship between learning conceptions and learning approaches. Next, the review focuses on the conceptions of learning uncovered in the Asian contexts, particularly the Chinese context. The article concludes that studies on the conceptions of learning are meaningful and conceptually helpful, thereby calling for more empirical and theoretical works.